Multi-parameter Test and Analysis of Dynamic Performance for Helical Gearboxes - Jia Shanhu; Lin Dong; Zhang Erliang (Jixie chuandong)
In order to evaluate the gearbox condition based on dynamic response, a helical gearbox test platform is built in the present work to test and analyze diverse physical parameters, including rotational speed, dynamic transmission error, axis orbit, vibration acceleration, sound pressure and load torque. By adjusting the working condition (shaft speed and load torque) of the gearbox, the assembly accuracy among the components of the gearbox is assessed, and the correlation between different physical parameters is revealed. The results show that the input shaft is misaligned with the motor shaft, and the output shaft suffers the dynamic unbalance; the peak-to-peak value of transmission error is positively correlated with rotational speed, and has a significant correlation with the root mean square value of acceleration and the peak-to-peak value of radial component of the output axis runout at different speeds.